Fighting Urinary Tract Infection: Fosfomycin’s Efficacy against Uropathogenic Escherichia coli Isolates - Sultana, Tania; Fakruddin, Md; Datta, Suvamoy; Shishir, Md Asaduzzaman (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Urinary tract infection (UTI) is one of the major health concerns of Bangladeshi women and the increase in antibiotic resistance among the uropathogens poses a serious threat to the public health. Objective: To explore the sensitivity of fosfomycin, an alternative antimicrobial agent, in comparison to other antibiotics currently in use against Escherichia coli. Methods: The urine samples were inoculated on MacConkey agar medium following standard bacteriological technique and incubated overnight at 37°C. Then the plates were examined for bacterial growth and biochemical tests were performed. The efficacy of different antibiotics was assessed against the isolates by Kirby Bauer’s disc diffusion method. Results: About 63.6% (350) of the urine samples (n= 550) were found to be culture positive. Among them, 20% of the isolates were presumed to be Escherichia coli, the most prevalent species, and further biochemical tests helped to confirm their identity. While considering the age group, incidence rate was higher among the young people of 21-30 years, especially women being the predominant. Resistance against different antibiotics was observed by these isolates and the highest was against Ciprofloxacin (90%) followed by Cotrimoxazole (75%), Meropenem (60%) and Amoxiclav (55%). Contrarily, the highest sensitivity was found against Fosfomycin (75%) and it could be the current drug of choice for treating UTI. Conclusion: Although the efficacy of Fosfomycin could be observed against the multi drug resistant (MDR) E. coli, continuous effort is required to generate a library of alternative antibiotics and their use should be rotated appropriately. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 338-343